2011
DOI: 10.1177/1470320310392617
|View full text |Cite
|
Sign up to set email alerts
|

Impaired dipsogenic and renal response to repetitive intracerebroventricular angiotensin II (AngII) injections in rats

Abstract: The role of the central nervous system (CNS) in the control of blood pressure and hydrosaline homeostasis has been demonstrated by several studies. While circulating angiotensin II (AngII) tends to retain sodium by a direct renal action as well as through aldosterone release, stimulation of brain AngII receptors has been reported to induce natriuresis. Repetitive intracerebroventricular AngII injection was recently demonstrated to be capable of leading to desensitisation of the dipsogenic effect of AngII stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…22 The current study also confirmed that AngII, when microinjected into the lateral ventricle of conscious NP rats, produced a marked dipsogenic effect. 14,15 Additionally, for the first time, we demonstrate that the dipsogenic effect of i.c.v. 4 nmol AngII was significantly lower in the LP offspring than in NP rats.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…22 The current study also confirmed that AngII, when microinjected into the lateral ventricle of conscious NP rats, produced a marked dipsogenic effect. 14,15 Additionally, for the first time, we demonstrate that the dipsogenic effect of i.c.v. 4 nmol AngII was significantly lower in the LP offspring than in NP rats.…”
Section: Discussionmentioning
confidence: 97%
“…dose-response AngII (at 40 pmol to 40 nmol) injection: rats received 2 µl AngII and the volume of water consumed was measured during the next 30 min. 14,15 …”
Section: Protocols For Angii Thirst-induction Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…33,34 A previous study reported that, in conscious rats, central AngII induces an immediate reduction in the efferent renal nerve and enhanced renin-angiotensin dipsogenic and natriuretic response. 17,35,36 Otherwise, further studies are needed to evaluate the repercussion of taurine supplementation directly on kidney morphology and development, and vascular reactivity.…”
Section: Discussionmentioning
confidence: 99%